1997
DOI: 10.1038/nm0697-651
|View full text |Cite
|
Sign up to set email alerts
|

Long-term protection of chimpanzees against high-dose HIV-1 challenge induced by immunization

Abstract: A combination AIDS vaccine approach consisting of priming with adenovirus-HIV-1MN gp160 recombinants followed by boosting with HIV-1SF2 gp120 was evaluated in chimpanzees. Long-lasting protection, requiring only three immunizations, was achieved against a low-dose challenge with the SF2 strain of HIV-1 and a subsequent high-dose SF2 challenge administered 1 year later without an intervening boost. Notably, neutralizing antibody responses against both clinical and laboratory isolates developed in three chimpanz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(92 citation statements)
references
References 39 publications
2
90
0
Order By: Relevance
“…Adenovirus-vectored recombinant vaccines expressing a wide array of antigens have been constructed and protective immunity against different pathogens has been demonstrated in animal models [21][22][23][24][25]. In our research, we demonstrated the efficacy of using an adenovirus-based vaccine for single-time genetic vaccination that provided long-lasting protective immunity against botulism caused by botulinum neurotoxin type C.…”
Section: Introductionmentioning
confidence: 72%
“…Adenovirus-vectored recombinant vaccines expressing a wide array of antigens have been constructed and protective immunity against different pathogens has been demonstrated in animal models [21][22][23][24][25]. In our research, we demonstrated the efficacy of using an adenovirus-based vaccine for single-time genetic vaccination that provided long-lasting protective immunity against botulism caused by botulinum neurotoxin type C.…”
Section: Introductionmentioning
confidence: 72%
“…A number of different vaccine carriers have been tested preclinically as well as in part clinically for induction of CD8 + T-cell responses to HIV-1. [28][29][30][31][32][33] Here we compared simian Ad vectors that varied with regard to deletions and insert lengths to determine which types of constructs are most suitable for further clinical development. DE1AdC68 and DE1/E3AdC68 vectors showed favorable growth characteristics and yields commonly exceeded those of AdHu5 vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this scenario, evidence exists that a sterilizing immunity against different HIV virus strains could be achieved. In chimpanzee HIV Env-based vaccines and in macaques live attenuated simian immune deficiency virus (SIV) vaccines protected from homologous and heterologous challenge [29][30][31][32][33]. In addition, reduction of viral loads following mucosal challenge with SIV was reported in rhesus macaques primed with recombinant Adenovirures expressing HIV Env and boosted with the recombinant protein [10,13,34].…”
mentioning
confidence: 99%